Prediction of Augenol in Cinnamon (Cinnamomum burmannii) Boiled as a Carminative to Overcome Floating Stomach - Rika Wahyu Pujiastini; Fendy Prasetyawan; Yuneka Saristiana; M. Wahyu Ariawan; Muhammad Nurul Fadel; Emma Jayanti Besan (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Flatulence (meteorismus) is a common condition caused by excess gas accumulation in the digestive tract. One alternative traditional treatment to overcome this condition is the use of herbal plants, such as cinnamon (Cinnamomum burmannii). This study aims to predict the potential of eugenol, an active compound in cinnamon, as a carminative agent using an in silico approach. Data were obtained from PubChem and analyzed using PASS Online to predict its pharmacological activity. The results of the analysis showed that eugenol has a probability of activity as a carminative of 0.941 and a probability of inactivity of 0.001, indicating high potential in helping to relieve flatulence. Thus, eugenol in cinnamon has the potential as an alternative natural treatment to overcome digestive disorders, especially bloating.